Changes in germination ability during genebank storage at some medicinal plant seeds belonging to the Solanaceae family - Tóth, E. (International Journal of Horticultural Science, 2001)
In the present work we have examined the changes of germination ability of some medicinal plant species belonging to the Solanaceae family (Datura stramonium L., Datura innoxia Mill. and Hyoscyamus niger L.) during 5-6 years’ storage period. According to our results, all the three species showed an after-ripening behavior. Potassium nitrate and gibberellic acid increased significantly the rate of germination in the case of Datura species. During the storage period tested (1995-2001), the species maintained their germination ability which is favourably but not significantly influenced by the cooled gene bank conditions. The degree of ripeness affected considerably the proportion of germinated seeds at all the three species. As a consequence of our results we emphasise that propagation with completely ripe seeds is proposed, however, half-ripe seeds developped in an unadvantageous vegetation period can be also utilized in the practice. The effect of vegetation year on stramony seeds manifested in the length of after-ripening period, while in the case of henbane the germination ability was also influenced.